TINJAUAN LITERATUR MEKANISME ZIKIR TERHADAP KESEHATAN: RESPONS IMUNITAS - Tri Niswati Utami (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2017)
ABSTRACT Health is an optimum (balanced) condition for the individual, physically, mentally, socially and spiritually and free of disease, disability and weakness. Unstable physical and mental conditions can cause physiological changes in the body. The instability of the level of perception or consciousness causes emotional distress such as: anger, sadness, depression, anxiety and so on. The purpose of this literature review is to explain the mechanism of zikr on health through an immune response. The method used in the study literature collects literature in the form of journals, books, reports and research documents.The relationship between the brain and the immune system occurs through the HPA axis, which involves hormones - cytokines, through cells contained in the ANS (automic nerve system) pathways. The balance will be responded by a body system such as a hormone. A balanced body system affects hormonal balance, is in a physiological state. The immune system or immune system is affected by physical, mental and social stressors. Severe stressors activate the HPA axis and sympatho adrenal medullary system (SAM), affecting metabolic changes and affecting the body's immune system against disease.Conclusion: zikrah improves spiritually and at a high level of consciousness, acts as a filter against emotional instability. Spiritual awareness can be activated internally and externally. Internal comes from within the individual such as: experience and externally activated by others through motivation. Key Words: zikr, immune system, health, body balance, physiological hormones, spiritual awareness.